Quick quiz #351. - Dalton, Michael (New Scientist, 2026)
The article primarily presents a cryptic crossword puzzle (#187) set by Trurl, accompanied by a quick quiz (#351) with science and general knowledge questions. The crossword clues and answers cover a range of topics including literature, mathematics, chemistry, and geography, while the quiz addresses subjects such as quantum computing, astronomy, and mathematics. Answers to both the crossword and quiz are provided, facilitating self-checking for readers. The content is designed for puzzle enthusiasts and researchers interested in cryptic crosswords and general knowledge challenges.